Status Gizi dan Keterpaparan Media Meningkatkan Kejadian Menarche Dini pada Siswi - Sadiman Sadiman; Islamiyati Islamiyati (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2019)
Background: The more children who experience early menarche, the greater the risk of children experiencing malignancy, including cancer, especially breast cancer. Excessive nutrition and media exposure are factors that trigger early menarche. Purpose: This study is to determine the analysis of factors associated with the incidence of early Mmenarche. Methods: This study used a cross sectional design with a population of students of SMP Negeri 4 Metro. The sample size of the study was 167 students taken by the symple random sampling technique. Variables measured by observations and questionnaires included the occurrence of early menarche (dependent variable) and nutritional status, the age history of maternal menarche and mass or electronic media exposure (independent variable). Data analysis using chi-square test. Results: The results showed that factors related to early menarche were nutritional status (p = 0.009; POR = 2.45) and electronic media exposure (p = 0.046; POR = 2.49). Conclusions: Factors of nutritional status and exposure to electronic media increase the incidence of early menarche. Efforts are needed to prevent early menarche among others by maintaining good nutritional status and reducing the brightness of electronic media.